Torsion of hematosalpinx with bicornuate uterus - Singh, Ila; Sarkar, Avir; Singh, Nilanchali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Torsion of fallopian tube is less frequent but significant cause of lower abdominal pain in reproductive age women that is difficult to recognize pre-operatively. Most of the cases with isolated fallopian tubal torsion have a delayed diagnosis and a subsequent delay of timely intervention that may result in failure to save the tubal function. Here we present a case of 22 years old female with torsion of hematosalpinx who presented with chronic lower abdominal pain that was successfully treated. Pre-operative imaging was non-specific. Laparoscopic detorsion and salpingectomy was performed, successfully preserving the ovaries.